Patients with advanced pancreatic and biliary cancer appear vulnerable to SARS-CoV-2 Omicron variant: An observational study during the COVID-19 outbreak in Shanghai - Han, Tao; Chen, Lujun; Gu, Jia; Wu, Shen; Maihemuti, Maiweilan; Yang, Jue; Wang, Hao; Wu, Jun; Zhang, Yue; Cong, Yun; Wang, Jiening; Chen, Tingsong (Frontiers in Oncology, 2023)
Background The COVID-19 pandemic has spread rapidly across the globe. Cancer patients have a higher risk of severe infections and associated mortality than the general population. However, the lethal effect of Omicron-variant affection on advanced pancreatic and biliary cancer patients is still not clear. Herein, we designed an observational study to shed light on the influence of the Omicron variant on this so-called “King of Cancer” and improve management of these patients with COVID-19 in the future. Methods Omicron-infected patients with advanced pancreatic and biliary cancer were enrolled from 15 April to 31 May 2022. Four groups were set up in this study: Group 1, Omicron-infected cancer patients (N = 4); Group 2, non-infected cancer patients (N = 4); Group 3, infected non-cancer-afflicted subjects (N = 4); Group 4, non-infected non-cancer-afflicted subjects (N = 4). On Days 0, 7, and 14 after infection, the blood samples were collected dynamically from all subjects. The primary endpoints were disease severity and survival. Results At the endpoint of this observational study, Patient Nos. 2, 3, and 4 died separately on Days 11, 25, and 13 after viral infection. All of them had advanced cancer, with a death rate of up to 75%. Group 1 presented an overall T-cell exhaustion status compared with other groups. Group 1 had obviously lower T-cell populations and higher B-cell percentages and CD4+T/CD8+T ratios (P <0.05). Time-course cytokine monitoring results showed that IL-1β was significantly decreased in Group 1 (P <0.05) and generally kept at a low level without obvious fluctuation. IL-6 was markedly increased in infected cancer patients (P <0.01) but remained at a low level and had no apparent change during the whole infection process in non-cancer-afflicted subjects. Furthermore, several inflammatory parameter indexes indicated a tight association of Omicron infection with the disease course and prognosis of Omicron-infected cancer patients. Conclusions Advanced pancreatic and biliary cancer patients with Omicron infection have severe symptoms and poor outcomes. More attention, protective measures, and routine healthcare services should be recommended to these vulnerable populations in clinical practice during the pandemic in the foreseeable future.